The effect of brand trust and store atmosphere on customer loyalty PT. Rotte Variety of Taste Branch Delima Panam Pekanbaru - Dara Dita Pahlewi; Zulher Zulher; Litra Diantara (Jurnal Riset Manajemen Indonesia, 2022)
This research aims to determine brand trust and store atmosphere on customer loyalty at PT. The rotte is like the taste of the Pekanbaru Panam Pomegranate Branch. the types and sources of data used in this study are primary data and secondary data, on the other hand the method of retrieval of this information is by using questionnaires, file research, observations, and interviews, the analysis used in this study is multiple linear analysis with the number of respondents as many as 96 people, The hypothesis is carried out with and t. Based on the results of the study, it can be opened if simultaneously brand trust and store atmosphere affect customer loyalty, while partially testing brand trust and store atmosphere based on customer loyalty, the closeness between the variables independently of the variables ensures that it is very strong with the contribution of the independent variable to the variable is 67.5%